2017
DOI: 10.1161/strokeaha.117.016720
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Multicenter Trial of ARTSS-2 (Argatroban With Recombinant Tissue Plasminogen Activator for Acute Stroke)

Abstract: Background and Purpose We conducted a randomized exploratory study to assess safety and the probability of a favorable outcome with adjunctive argatroban, a direct thrombin-inhibitor, administered to rt-PA treated ischemic stroke patients. Methods Patients treated with standard-dose rt-PA, not receiving endovascular therapy, were randomized to receive no argatroban or argatroban (100-μg/kg bolus) followed by infusion of either 1 μg/kg/min (low-dose) or 3 μg/kg/min (high-dose) for 48 hours. Safety was inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 26 publications
7
54
2
Order By: Relevance
“…It has been reported that the combination of IV-tPA and argatroban is effective and safe against acute ischemic stroke (AIS). 18) It has also been reported that IV-tPA was effective and safe against AIS caused by CeAD. 19) Cohen et al reported findings on EVS for iLAO caused by eICAD.…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that the combination of IV-tPA and argatroban is effective and safe against acute ischemic stroke (AIS). 18) It has also been reported that IV-tPA was effective and safe against AIS caused by CeAD. 19) Cohen et al reported findings on EVS for iLAO caused by eICAD.…”
Section: Discussionmentioning
confidence: 95%
“…The symptomatic ICH rates were 10%, 13%, and 7%, respectively. The rates of those with mRS 0-1 in the third month were 21%, 30%, and 32%, respectively (48). Therefore, this combination is practical and safe and should be tested in further studies.…”
Section: Question: What Strategy Should Be Used For IV Tpa Administramentioning
confidence: 95%
“…1 Compared to r-tPA alone, ARTSS-2 demonstrated safety and improved clinical outcomes in patients that received combination r-tPA and argatroban. In general, we are in complete agreement with Dr. Shah’s comments and would like to make the following points.…”
Section: In Responsementioning
confidence: 98%